1983
DOI: 10.1017/s0007485300013821
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, biology and host specificity of Cyrtobagous singularis Hustache (Coleoptera: Curculionidae) for the biological control of Salvinia molesta

Abstract: Cyrtobagous singularisHust. was recorded from Brazil, Paraguay,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 6 publications
4
48
0
Order By: Relevance
“…Significant difference in weevil mortality was observed between 2.3% and 6.9% (Table 5) deltamethrin deposition and did not show significant mortality at less than 2% deposition as determined from the aluminium foils (Kurugundla & Serumola, 2007;Kurugundla et al, 2010). The fluctuations in the abundance of weevils in the field Salvinia infestations at the sites of Xakanaxa ( Figure 2) and Kwando ( Figure 3) after praying was due to the spatial distribution of weevils and to less breeding during winter (Forno et al, 1983;Naidu et al, 2000) despite some spray effects. In all five cycles the abundance of weevils in 20 standard plants was higher than one (Forno, 1987) showing that weevils maintained their equilibrium at Shummamori, Hamokata, Lebala and Selinda (Figure 3) during the spray programme.…”
Section: Aquatic Plants (Salvinia Molesta) and Biological Control Weementioning
confidence: 87%
See 1 more Smart Citation
“…Significant difference in weevil mortality was observed between 2.3% and 6.9% (Table 5) deltamethrin deposition and did not show significant mortality at less than 2% deposition as determined from the aluminium foils (Kurugundla & Serumola, 2007;Kurugundla et al, 2010). The fluctuations in the abundance of weevils in the field Salvinia infestations at the sites of Xakanaxa ( Figure 2) and Kwando ( Figure 3) after praying was due to the spatial distribution of weevils and to less breeding during winter (Forno et al, 1983;Naidu et al, 2000) despite some spray effects. In all five cycles the abundance of weevils in 20 standard plants was higher than one (Forno, 1987) showing that weevils maintained their equilibrium at Shummamori, Hamokata, Lebala and Selinda (Figure 3) during the spray programme.…”
Section: Aquatic Plants (Salvinia Molesta) and Biological Control Weementioning
confidence: 87%
“…On cold nights the weevils normally hide in buds, roots and beneath the leaves. They deposit their eggs in buds and underneath leaves, and emerging larvae normally feed inside the rhizome (Forno et al 1983). Therefore adults and larvae would often be protected from contact with the insecticide (Schlettwein & Giliomee, 1990 Kurugundla et al, 2010).…”
Section: Aquatic Plants (Salvinia Molesta) and Biological Control Weementioning
confidence: 99%
“…Comparative studies determined that this was a new species, subsequently named Cyrtobagous salviniae by Calder and Sands [88]. Host range studies to assess feeding by C. salviniae were carried out in Australia on six plant species [89]. Several other insect species, various fungi, and a snail have been reported attacking salvinia in its exotic range and none has been reported to be effective on the weed [90].…”
Section: Biological Control Agentsmentioning
confidence: 99%
“…Larvae browse the young buds, the "roots" and tunnel the rhizome. Increased nitrogen stimulates an increase in oviposition [92] and feeding increases with increased temperature [89]. The combined effect of feeding by adults and larvae prevents growth by destroying meristematic tissues and destroying rhizomes, severing the root-shoot link.…”
Section: Biological Control Agentsmentioning
confidence: 99%
“…In South America, Forno et al (1983) observed C. salviniae (at that time thought to be C. singularis) attacking Salvinia spp. and not feeding on plants that grow in association with it (waterfern (Azolla spp.…”
Section: Host-specificitymentioning
confidence: 99%